Isolation, characterization and cytotoxic effect exploration of methanolic extract of local medicinal plant clerodendrumn viscosum vent - Abdul Kalam, Azad; Wan Sulaiman, Wan Mohd. Azizi; Tengku Zakaria, Tengku Muhamad Faris Syafiq; S., Mahmood; H. A., Almoustafa; Labu, Zubair Khalid (INSI Publications, 2013)
Clerodendrumn viscosum vent. is a majestic and broadly used medicinal plant in Bangladesh and India. This research work was carried out to evaluate the phytochemical and biological activity of Clerodendrum viscosum vent. The powdered barks of the roots were extracted with ethanol by a soxhlet apparatus. Ethanol extract was subjected to TLC (Thin Layer Chromatography) examination. A single spot was observed in n-hexane ethyl acetate (4:1) with Rf values 0.5. Phytochemical screening of the ethanol extract showed the presence of carbohydrates, steroids, tannins, flavonoids, saponines and alkaloids. The crude ethanol extract showed toxic behavior against brine shrimp lethality bioassay. The mortality rate of brine shrimp was found to be increased with the increase in concentration of the sample. From the result on the brine shrimp lethality bioassay it can be well predicted that the crude extracts have considerable cytotoxic potency.